The faithful: a history of Catholics in America - O'Toole, James M. (Belknap Press of Harvard Univ. Press, 2008)
The priestless church -- The church in the Democratic Republic -- The immigrant church -- The church of Catholic action -- The church of Vatican II -- The church in the twenty-first century